Management of Posterior Fossa Tumors in Adults Based on the Predictors of Postoperative Hydrocephalus - Zhang, Chengda; Zhang, Tingbao; Ge, Lingli; Li, Zhengwei; Chen, Jincao (Frontiers in Surgery, 2022)
Objective: To identify the predictors of postoperative hydrocephalus in patients with posterior fossa tumors (PFTs) and guide the management of perioperative hydrocephalus. Methods: We performed a retrospective analysis of patients who had undergone resection of PFTs at the Department of Neurosurgery in Zhongnan Hospital of Wuhan University between January 2011 and February 2021. Patients were divided into either the prophylactic external ventricular drainage (EVD) group or the non-prophylactic EVD group. We analyzed the non-prophylactic EVD group to identify predictors of acute postoperative hydrocephalus. We analyzed the two groups simultaneously to determine predictors of postoperative ventriculoperitoneal(VP) shunt placement. Results: Tumor infiltration of the midbrain aqueduct (P=0.001; OR=9.16), postoperative hemorrhage (P<0.001; OR=71.46), and subtotal resection (P=0.006; OR=9.23) were independent risk factors for postoperative EVD. Tumor infiltration of the lower half or the inferior of the fourth ventricle (P=0.014; OR=12.83), tumor infiltration of the upper half of the fourth ventricle (P< 0.001; OR=975.02), tumor infiltration of the midbrain aqueduct (P< 0.001; OR=342.57), and postoperative hemorrhage (P< 0.001; OR=35.86) were independent risk factors for postoperative VP shunt placement. Total resection of the tumor (P=0.024; OR=0.14) was an independent protective factor. Conclusions：Tumor infiltration of the midbrain aqueduct, postoperative hemorrhage, and subtotal resection were independent risk factors for the development of acute hydrocephalus after the resection of PFTs. Tumor infiltration of the infratentorial midline ventricular system, postoperative hemorrhage, and subtotal resection were independent risk factors for the development of persistent hydrocephalus after resection of PFTs, and preoperative EVD did not reduce its incidence.